HUBUNGAN PARITAS DENGAN KEJADIAN PERDARAHAN PADA IBU POST PARTUM DI BPS NY. N DI DESA KLAGEN SERUT KECAMATAN JIWAN MADIUN - Etika Desi Yogi; Sinta Ayu Setiawan; Sri Dwi Hastuti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
Maternal Mortality Rate in East Java 2011 were 101.40 per 100,000 births. The of incidence of maternal mortality in East Java in 2011 was caused by direct obstetric or the bleeding. Factors that lead to postpartum hemorrhage include the presence of uterine atony, retained placenta, lacerations of the birth canal and the blood clotting factor, whereas postpartum hemorrhage predisposing factors that include hydramnios, gemeli, parity and age. Data from the Madiun County Health Department in 2011 found bleeding number 230 of 12 698 maternal. At BPS Ny. Niniek Soelasminingsih, S.ST in 2011 from 58 deliveries got the bleeding as much as 6 patients deliver within 24 hours post partum, 2 people tear the multiparous born 4 cases with uterine atony. This study aims to determine the relationship of parity with the incidence of post-partum bleeding. Type of study is the correlation with the analytic case-control approach. Collecting data using retrospective data. Samples from this study were all mothers giving birth at BPS Ny Niniek Soelasminingsih, S.ST from the medical records of a total of 61 maternal. The study was conducted in November 2012, the data were analyzed using Chi Square statistical test with a significance level set at p ≤ 0.05. The results showed that the number of women who experience bleeding as many as 12 people, most bleeding is multiparitas mothers by 5 people. Having analyzed by chi-square statistical test results showed no association between parity and incidence of postpartum hemorrhage in BPS Ny. Niniek Soelasminingsih S.ST 0.008 with p value ≤ 0.05 in other words Ha received. Recommended that the delivery assistance by personnel who are competent so that the incidence of postpartum hemorrhage can be treated as good as possible so that the maternal mortality rate in Indonesia could be on tap as well as early detection of high risk pregnant women and maternity over increased.